2023
DOI: 10.1111/bjh.18813
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GBT1118, a voxelotor analog, on intestinal pathophysiology in sickle cell disease

Abstract: Voxelotor is an allosteric haemoglobin (Hb) modulator that binds covalently and reversibly to Hb alpha chain to facilitate improved Hb-O 2 affinity and arterial oxygen. It, therefore, reduces the susceptibility of erythrocytes carrying Haemoglobin S to sickle. In this study, we have used GBT1118, an analog of voxelotor, to treat male Townes sickle cell disease (SCD) mice to investigate whether the Hb modulator could attenuate the intestinal pathophysiologic changes associated with SCD. Compared with mice fed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Other mechanisms of action have recently been attributed to the therapeutic effect of voxelotor in SCD. A study by Tarasev et al explored the effect of GBT1118, a voxelotor analog, on hypoxia-induced lethal and sub-hemolytic RBC membrane damage [27,28]. Findings indicated that GBT1118 prevented hypoxia-induced membrane damage in sickled RBCs, indicating that voxelotor may also act through other mechanisms not related to hemoglobin-oxygen affinity.…”
Section: Voxelotormentioning
confidence: 99%
“…Other mechanisms of action have recently been attributed to the therapeutic effect of voxelotor in SCD. A study by Tarasev et al explored the effect of GBT1118, a voxelotor analog, on hypoxia-induced lethal and sub-hemolytic RBC membrane damage [27,28]. Findings indicated that GBT1118 prevented hypoxia-induced membrane damage in sickled RBCs, indicating that voxelotor may also act through other mechanisms not related to hemoglobin-oxygen affinity.…”
Section: Voxelotormentioning
confidence: 99%